Application Of Hec-Ras Hydrodynamic Flood Modelling For River A Study Case Of Bertam Valley, Pahang - Andrew, Lee Kwan Yee (Universiti Sains Malaysia, 2021)
Dams are built to store water to adapt for changes in the catchment region, and they are undeniably one of the most efficient renewable energy sources. The dam will open the sluice gate to discharge certain amount of water when the level of water is almost exceeding the safety level of it. However, an overwhelming amount of discharges discharged from the dam's gated spillways would cause egregious damage to the downstream area. As a result, a study was conducted on the effects of various maximum discharges on the flow along a segment of the downstream river in Bertam Valley. The highlighted objectives for the study were to simulate a flood inundation of Bertam Valley using HEC-RAS model and to have validation and comparison of HEC-RAS model based on discharge value and water level. With HEC-RAS, a computer simulation was run to examine various maximum discharges released from the dam's gated spillway. The amount of water release used in the simulation were 10, 27.5, 75, 230 and 300 m³/s based on the recommendation dam release by Tenaga Nasional Berhad (TNB), according to a previous study. The result shows that the safest maximum release was 27.5 m³/s, that is when water started to overflow from the bank. The water depth, and velocity, as well as the travel time of the water flow at the discharge of 27.5 m³/s are 2.66 m, 1.33 m/s and 0.22 hour respectively. The study could be useful for warning to local inhabitants and to help dam management in controlling the amount of maximum discharge level from the dam.